Ecotin: A versatile protease inhibitor of bacteria and eukaryotes - De Meyer, Frédéric; Carlier, Aurélien (Frontiers in Microbiology, 2023)
Serine protease inhibitors are a large family of proteins involved in important pathways and processes, such as inflammatory responses and blood clotting. Most are characterized by a precise mode of action thereby targeting a narrow range of protease substrates. However, the serine protease inhibitor ecotin is able to inhibit a broad range of serine proteases that display a wide range of specificities. This specificity is driven by special structural features which allow unique flexibility upon binding to targets. Although frequently observed in many human/animal-associated bacteria, ecotin homologs may also be found in plant-associated taxa and environmental species. The purpose of this review is to provide an update on the biological importance, role in host-microbe interactions and evolutionary relationship between ecotin orthologs isolated from Eukaryotic and Prokaryotic species across the Tree of Life.